Status of nutritional practices for domestic cows in rural ecology of north-western Indo-Gangetic plains - KUMAR, PRAVENDRA; SINGH, RAJBIR; PANWAR, PRATAP SINGH (The Indian Journal of Animal Sciences, 2015)
Data congregated on 150 households from 15 ecosystems in rural area of Baghpat district of north-western Indo-Gangetic plains. The overall body weight of cows was 376.1 ± 8.8 kg and overall daily milk yield was 4.76 ± 0.08 kg. On an average, a cow requires 9.4 ± 0.09 kg dry matter daily; whereas, only 8.46 ± 0.07 kg dry matter could be supplied leaving a 10 % deficiency of dry matter, which was significantly affected by the lactation order. The daily digestible crude protein (DCP) availability to a cow were 0.47 ± 0.008 kg and 0.43 ± 0.005 kg indicating a deficiency of 0.04 kg DCP/ day/ cow. The requirement as well as availability of DCP for cows was affected significantly by lactation order. The requirement and availability of total digestible nutrients (TDN) were 4.47 ± 0.10 kg and 3.96 ± 0.05 kg/day for cows, showing a deficiency of 8.85 %. The lactation order and herd size affected significantly the requirement as well as the availability of TDN for cows.